Potensi dan Tantangan Penataan Ruang, Infrastruktur, Kesejahteraan dan Produktivitas Pembangunan, Desa Kanjilo, Kecamatan Barombong, Kabupaten Gowa - Yashinta Kumala Dewi Sutopo; Ahmad Fauzi Budjang; Regita Chahyani Abdul Gani; Rizkiyah Amaliah Fadila; Syifa Beby Alisha (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Kanjilo Village is a rural administrative area located in Gowa Regency, South Sulawesi Province. Activities in the Kanjilo Village contribute quite high to the Gowa Regency region, especially the agriculture and industry sectors. Based on these conditions, it encourages researchers to identify the potential and resources of the Kanjilo Village. The purpose of this identification is to broaden the knowledge of the community and local government related to the existing conditions of the territory. So that it can be a reference material in planning an independent Kanjilo Village in accordance with Law No. 6 of 2014 concerning the role of villages in national development. The method used in this research is descriptive qualitative. This method describes or depicts the object of research based on facts that appear or as they are.